2019
DOI: 10.1016/j.jaci.2018.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Severe combined immunodeficiency in stimulator of interferon genes (STING) V154M/wild-type mice

Abstract: STING gain-of-function mice developed an interferon-independent SCID phenotype with a T-cell, B-cell, and natural killer cell developmental defect and hypogammaglobulinemia that is associated with signs of inflammation in lungs and kidneys. Only the intrinsic proliferative defect of T cells was partially interferon dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 43 publications
(76 reference statements)
8
77
1
Order By: Relevance
“…S2A). This was consistent with the findings of other investigators who also observed a minimal ISG signature as a result of SAVI mutations (16,17). This result was surprising because murine models of two additional STING-dependent type I interferonopathies, TREX1-deficient mice (5) or DNase II-deficient mice (19), had robust ISG signatures.…”
Section: Savi Mutant Mice Have Elevated Type I Ifn and Inflammatory Genesupporting
confidence: 92%
See 1 more Smart Citation
“…S2A). This was consistent with the findings of other investigators who also observed a minimal ISG signature as a result of SAVI mutations (16,17). This result was surprising because murine models of two additional STING-dependent type I interferonopathies, TREX1-deficient mice (5) or DNase II-deficient mice (19), had robust ISG signatures.…”
Section: Savi Mutant Mice Have Elevated Type I Ifn and Inflammatory Genesupporting
confidence: 92%
“…Despite the severe phenotypes of many SAVI patients, the same mutation in different individuals can have very different clinical manifestations (13)(14)(15). Thus, a better understanding of how, when, and where overactivation of STING causes sterile inflammation is clearly needed and animal models have been developed by investigators to explore these questions (16,17). Unexpectedly, murine models of the two most common SAVI mutations appear to reflect different aspects of the human disease: the N153S mutant mice purportedly develop skin disease while the V154M mice were found to develop variable levels of lung inflammation.…”
mentioning
confidence: 99%
“…Interestingly, the most frequent virus isolated was rhinovirus, which may be a direct consequence of effective type I IFN inhibition by ruxolitinib at least in respiratory epithelial cells, where IFN-β is required to control rhinovirus [16,17]. On the other end, these infections might result from a cumulative effect of the drug with the reported developmental and in vitro proliferative defects of STING mutant T lymphocytes [18,19]. Considering the severity of lung disease and the lymphopenia ( Table 2) present before ruxolitinib treatment, P2 was started on antibiotic prophylaxis with Bactrim and Azithromycin; that, however, did not seem to prevent the febrile episodes, mostly if not always caused by viral pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulator of interferon genes -associated vasculopathy with onset in infancy (SAVI) is a typical STING-related hereditary inflammatory type-I interferonopathy, and is manifested by interstitial lung disease, dermatomyositis and arthritis. Its pathology is featured by leukocytoclastic vasculitis and microthrombotic angiopathy of small dermal vessels (166,167) and patients can also suffer from lymphopenia (166)(167)(168)(169). The etiology of SAVI is a gain of function (GOF) mutant in STING which leads to constitutive STING activation without CDNs stimulation (166).…”
Section: Cgas-sting Pathway In Autoimmune or Inflammatory Diseasesmentioning
confidence: 99%
“…The inhibitory role of cGAS-STING in inflammation is also attributed to its apoptosis-triggering role. In some subtypes of SAVI and mouse models, apoptosis of blood-vessel endothelial cells or bronchial epithelial cells and leucopenia can be observed (especially T-cell lymphopenia) (166,169,170). When the STING signal is stimulated, apoptosis occurs more frequently in normal or cancerous T cells (119).…”
Section: Cgas-sting Pathway In Autoimmune or Inflammatory Diseasesmentioning
confidence: 99%